Social interaction within the village migrant circular pins town of Banda Aceh, Indonesia - Rusli Yusuf (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2013)
The research was conducted in Peuniti Banda Aceh, with the objective of identifying and assessing the realization of social integration and social conflicts that occurred among migrants, and among migrant populations "original" Peuniti which is urban slum village (slum areas). To find and assess the influence of regional origin of heterogeneous circular migrants to the possibility of social integration and social conflicts that took place in the process of social interaction. The aim of this study is to know and study the process of adaptation among migrants and between migrants with local residents, furthermore, to know and assess the social and demographic characteristics, education and economic migrants circular. Social and demographic characteristics include: age, sex, marital status and religion. Educational characteristics include: education and skills. Economic characteristics include: type of job, income, working hours and work location. Another important reason for conducting this research is to find and examine the reasons for living in Peuniti circular migrant. The selected respondents are 107 people. Methods of data analysis used method of frequency tabulation and cross tabulation. In addition, to the use of cross tabulation method is to determine the size of the effect caused by the size of the frequency and percentage. The results allegedly embodiment of social interaction is more dominant than the conflict social have a positive relationship between fellow migrants from the same area. There is also a positive relationship between bonds of different areas. Most migrants have education and low skills, age and productive work in the sector informal. Migrant prefers residing in Peuniti for reasons closer to the workplace and ease of transportation and the rent is relatively cheap hostels